2021
DOI: 10.3389/fimmu.2021.734110
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Single Chain Variable Fragments From HIV Broadly Neutralizing Antibodies Demonstrate High Potency and Breadth

Abstract: Broadly neutralizing antibodies (bNAbs) are currently being assessed in clinical trials for their ability to prevent HIV infection. Single chain variable fragments (scFv) of bNAbs have advantages over full antibodies as their smaller size permits improved diffusion into mucosal tissues and facilitates vector-driven gene expression. We have previously shown that scFv of bNAbs individually retain significant breadth and potency. Here we tested combinations of five scFv derived from bNAbs CAP256-VRC26.25 (V2-apex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that a cocktail of several scFvs targeting different molecular epitopes could enhance sensitivity of scFv-based disease detection and improve disease prevention potency when compared with individual scFvs ( 54 , 55 ). Therefore, we combined four scFvs against the PEDV N protein to explore their efficacy in preventing PEDV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that a cocktail of several scFvs targeting different molecular epitopes could enhance sensitivity of scFv-based disease detection and improve disease prevention potency when compared with individual scFvs ( 54 , 55 ). Therefore, we combined four scFvs against the PEDV N protein to explore their efficacy in preventing PEDV infection.…”
Section: Discussionmentioning
confidence: 99%
“…To improve neutralization coverage, appropriate bNAb combinations with proven synergistic effects may be used in place of bNAb monotherapy. Modelling, in vitro and in vivo studies have shown that bNAb combinations offer improved neutralisation coverage and potency over bNAb monotherapy [27][28][29][30]. Moreover, in a phase Ib clinical trial (NCT02825797), bNAb combination (3BNC117 and 10-1074) was shown to be more effective than bNAb monotherapy (3BNC117) at preventing viral rebound following treatment interruption (median viral rebound of 21 weeks and 6-10 weeks respectively) [31].…”
Section: Introductionmentioning
confidence: 99%